Pengelolaan Pembelajaran Matematika Berbasis Lingkungan Di SMP Negeri 2 Sambi Boyolali - Warsanto, Warsanto; , Prof. Dr. Budi Murtiyasa, M.Kom; , Dr. Sofyan Anif, M.Si (2015)
This study aimed to describe: 1) planning of mathematics learning based on environment, 2) implementation mathematics learning based on environment, and 3) factors that become obstacles environment-based mathematics learning at Junior High School State 2 Sambi-Boyolali. The research is a a qualitative research with naturalistic paradigm approach. Location of this research at Junior High School State 2 Sambi-Boyolali. Subjects in this study are teacherss, headmaster, students. Data collection techniques performed by the method of interview, observation and document. Data analysis technique using flow analysis. The results showed that 1) Planning of mathematics learning based on environment at SMP includes a) preparation of mathematics learning plan based on environment, b) teachers need to have: the ability to understand the norms of the learning planning process in accordance with KTSP, the ability to do the creativity and the development of lesson plan, adequate knowledge about environmental phenomena, c) teachers must be able to develop learning resources from the environment, d) preparation of illustration tool that can be used to describe the environment as a learning resource. Math lesson plans based environment associated with the student is the teacher to prepare one of the students as a field coordinator and a student again as providers and care infrastructure. 2) Implementation of environment-based mathematics learning at junior high school, are a) beginning learning activities provides an introduction to mathematics learning objectives are sourced from the environment; b) perform preliminary in the classroom or outside the classroom; c) explain the purpose of learning the preliminary activities in accordance with the lesson plan that had been developed previously; and d) preparing the necessary teaching aids. Implementation of environment-based mathematics instruction related to student teachers to provide information to students about the locations that will be used as a place of learning and giving assignments to students before the beginning of environment based learning implemented. 3) Constraints in environment based mathematics learning at junior high school are a) difficulty coordinating the students, because the students are very great enthusiasm; b) when the rainy season so that learning should always be done in the classroom; c) environment-based learning tools are practical, so its use should be shared with other subjects; d) learning location is difficult to pass for student, so students there fallen; and e) the location where learning is dirty and tarnish.